MANAGING HIGHER EDUCATION INSTITUTIONS BASED ON IMAGE AND COMMUNICATION POLICY IN THE REINTEGRATION OF WAR VETERANS INTO DIGITAL SOCIETY (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article establishes that modern society is a complex of relationships among individuals. It is noted that in Ukraine, due to military actions, there is a growing need to enhance the communicative and image policies of higher education institutions. The aim of the study is to develop an effective communication and image policy for higher education institutions during the reintegration of veterans into the digital society. Despite a sufficient volume of scientific research in the field of communication and image policy, the question of developing an approach to its implementation remains unresolved. Moreover, it is important to consider the combination of both policies and view them as a unified whole that complements each other. It is proven that in the process of reintegrating war veterans into the digital society, the goals of policy implementation can include: reproducing a recognizable image, improving reputation, increasing rating, maintaining constant contact with stakeholders, establishing communication channels, implementing innovations, crisis management, increasing security level, and strengthening resilience. It is outlined that a higher education institution, in reintegrating war veterans into the digital society, can implement various types of images, the most popular of which are corporate, content-based, and comparative. It is proposed that in developing an optimal communication and image policy for a higher education institution in the reintegrating of war veterans into the digital society, one should adhere to the author's methodology. It consists of four stages: defining the problem and possible alternative solutions, project planning, plan execution, control and verification of plan execution, reflection. The final stage is cyclical.
Keywords: image policy, communication policy, veterans' reintegration into society, management, reputation.